Hepatobiliary damage and changes in hepatic gene expression caused by the antitumor drug ecteinascidin-743 (ET-743) in the female rat - DONALD, Sarah; VERSCHOYLE, Richard D; GREAVES, Peter; GESCHER, Andreas J; EDWARDS, Richard; JUDAH, David J; DAVIES, Reginald; RILEY, Joan; DINSDALE, David; LOPEZ LAZARO, Luis; SMITH, Andrew G; GANT, Timothy W (Cancer research (Chicago, Ill.), 2002)
Ecteinascidin-743 (ET-743) is a novel marine-derived anticancer drug with clinical activity in soft tissue sarcoma and ovarian cancer. Reversible transaminitis and subclinical cholangitis have frequently been described in patients who receive ET-743. To facilitate understanding of this adverse effect and help design suitable therapeutic rescue strategies, we characterized the hepatic effects of ET-743 in rats. Female rats received ET-743 (single dose, 40 microg/kg) i.v., and liver changes were assessed from 6 h up to 3 months after dosing by histopathology, immunohistochemistry, electron microscopy, hepatic and plasma biochemistry, and DNA microarray analysis. At 24 h posttreatment and beyond, livers displayed degeneration and patchy focal necrosis of bile duct epithelial cells associated with mild inflammation followed by fibrosis. Sporadic and focal zones of hepatic necrosis and hemorrhage were observed from day 2 onward, although the majority of hepatocytes appeared normal as judged by electron microscopy. Pathological alterations persisted up to 3 months after dosing. Plasma levels of total bilirubin were elevated up to 7-fold over those in untreated rats from day 2 onward and returned to control values by day 24. Activities of alkaline phosphatase and aspartate aminotransferase in plasma were elevated for 2 and 3 months, respectively. Activities of the hepatic microsomal drug-metabolizing enzymes cytochrome P-450 A1/2, CYP2E1, and CYP3A2 were decreased. DNA microarray analysis of livers from ET-743-treated animals showed a dramatic increase in the expression of ATP binding cassette transport genes Abcb1a and Abcb1b, which impart resistance to anticancer drugs, and of Cdc2a and Ccnd1, the rodent homologues of human cell cycle genes CDC2 and cyclin D1, respectively. The cell cycle gene expression changes mirrored ET-743-induced increases in liver weight and Ki-67 labeling of liver nuclei. The results suggest that the toxicity exerted by ET-743 in the rat liver is a consequence of biliary rather than hepatocellular damage and that it is accompanied by a wave of mitogenic activity, which may be driven by the transcriptional increase in Cdc2a expression.